PENDIDIKAN, KETRAMPILAN, KEMAMPUAN DAN KEAKTIFAN KARYAWAN - Sri Andika Putri; Fitria Setyaningrum (Unitri Press, 2021)
The purpose of this research was to find out how far the relationship between the education possessed by the employees, the skills possessed, the abilities possessed and the activeness of the employees that can be utilized by the company in developing its business through partial and simultaneous quantitative analysis. Researchers took research data in CV. Cipta Karya Pratama Junrejo Batu city. The number of employees who were used as research samples were 30 people who were carried out randomly. The data was taken by means of documentation and giving questionnaires to employees where the validity of this questionnaire has been tested first. The results showed that the education variable is worth 6.013, the skill variable is 3.802, the ability variable is worth 3.793 so that these three variables are simultaneously significant. While the correlation coefficient between education, skills, abilities and activity is 87.4%, which means that these four things have a high relationship.